2021
DOI: 10.1186/s13041-021-00810-w
|View full text |Cite
|
Sign up to set email alerts
|

Novel epigenetic clock for fetal brain development predicts prenatal age for cellular stem cell models and derived neurons

Abstract: Induced pluripotent stem cells (iPSCs) and their differentiated neurons (iPSC-neurons) are a widely used cellular model in the research of the central nervous system. However, it is unknown how well they capture age-associated processes, particularly given that pluripotent cells are only present during the earliest stages of mammalian development. Epigenetic clocks utilize coordinated age-associated changes in DNA methylation to make predictions that correlate strongly with chronological age. It has been shown… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…ALS patient-derived iPSCs have provided unprecedented access to human diseased MNs, enabling researchers to follow the course of degeneration in a dish. Our ipMNs have a developmental age corresponding to 75–90 days post conception, similar to previous observations ( Ho et al., 2016 ; Steg et al., 2021 ). However, iPSC-derived neurons display disease-related phenotypes and dysregulated molecular pathways induced by the underlying mutations ( Dafinca et al., 2020 ; Fujimori et al., 2018 ; Hall et al., 2017 ; Mehta et al., 2021 ; Selvaraj et al., 2018 ).…”
Section: Discussionsupporting
confidence: 90%
“…ALS patient-derived iPSCs have provided unprecedented access to human diseased MNs, enabling researchers to follow the course of degeneration in a dish. Our ipMNs have a developmental age corresponding to 75–90 days post conception, similar to previous observations ( Ho et al., 2016 ; Steg et al., 2021 ). However, iPSC-derived neurons display disease-related phenotypes and dysregulated molecular pathways induced by the underlying mutations ( Dafinca et al., 2020 ; Fujimori et al., 2018 ; Hall et al., 2017 ; Mehta et al., 2021 ; Selvaraj et al., 2018 ).…”
Section: Discussionsupporting
confidence: 90%
“…They are commonly referred to as epigenetic clock (epiclock) and serve as reliable predictors of the biological age of organs. [18][19][20][21] Several studies have profiled methylation changes in the brain during aging 17,22,23 and in the developing brain at fetal stages and found that aberrant methylation in the fetal brain can influence the risk of brain diseases later in life. 24,25 Commonalities in morphometric changes have also been observed in the brain during development and aging.…”
Section: Introductionmentioning
confidence: 99%
“…Methylation, the majority of which occurs in CpGs (5’‐Cytosine‐phosphate‐Guanine‐3′) sites, changes in correlation with age. They are commonly referred to as epigenetic clock (epiclock) and serve as reliable predictors of the biological age of organs 18–21 . Several studies have profiled methylation changes in the brain during aging 17,22,23 and in the developing brain at fetal stages and found that aberrant methylation in the fetal brain can influence the risk of brain diseases later in life 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the maturation of PV neurons is protracted and exquisitely regulated by experience and cell-extrinsic factors ( Donato et al, 2015 ). Most currently available differentiation methods render immature or fetal cells ( Steg et al, 2021 ; Studer et al, 2015 ). This sets the stage for optimized methods, in which distinct cell types can be generated for mechanistic investigation.…”
Section: Discussionmentioning
confidence: 99%